Relevansi Undang-Undang Ketenagakerjaan dalam menjawab tantangan Remote Working di Indonesia - Amanda Fitriani Eka Putri (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Industry 4.0 is an emerging phenomenon that changes the industrial paradigm by combining digital and physical technology to create a production system that is more efficient, flexible and connected. The increasingly effective use of the internet for long distance communication has resulted in the disappearance of time and space boundaries in living life. In the industrial sector, this is exploited by the emergence of a remote work system that relies on the internet to support its work, namely a remote working system. With this remote working system, there are benefits felt by both the company and the workers. Even though it offers flexibility and efficiency, remote working also presents various challenges that need to be overcome, especially related to legal and employment aspects. Especially in terms of fulfilling the rights of remote working workers themselves. Therefore, in this context, the relevance of the Employment Law becomes increasingly important. Considering that there is still legal uncertainty and a legal vacuum regarding the provisions relating to the remote working system itself.